The Influence of Generative Learning Model Assisted with Wingeom Software to Student’s Mathematical Learning Outcomes - Yunio Hindriyanto; Meyta Dwi Kurniasih (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2018)
The purpose of the research aims at identifying the influence of student’s mathematical learning outcomes from a generative learning model assisted through Wingeom Software. The research was conducted at SMP 262 in April 2018 of the 2017/2018 academic year. The research employed a Quasi-Experiment method with cluster random sampling from two classes, that is, VIII-A and VIII-B. The research instrument used the test essay of student’s Mathematical learning outcomes of which the eight items considered as to be valid and reliable. The normality test was carried out by using Liliefors while the homogeneity test uses the Fisher test. The finding shows that class VIII-A taught by generative learning model assisted through Wingeom Software has higher values than the class with no generative learning model implementation. In conclusion, the average value of students taught by a generative learning model assisted through Wingeom Software is considered to be higher than the ones who are not imposed by the generative learning model.